THE HERCYNIAN ARBURESE TECTONIC UNIT OF SW SARDINIA. NEW STRATIGRAPHIC AND STRUCTURAL DATA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
New structural and biostratigraphic data, mainly based on conodonts, permit the recognition of three different sub-units within the Hercynian Arburese Tectonic Unit of SW Sardinia, which are here described. Some stages and conodont biozones of Silurian-Early Devonian age are reported for the first time in Sardinia.
Keywords: Arburese Tectonic Unit; Conodont biostratigraphy; Biosedimentology; Palaeozoic; Hercynian orogenesis; Sardinia.